دور النشاط الرياضي الترويحي في التخفيف من لعض المشاكل النفسية لدى المراهقين - بلعجال, مصطفى (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
تهدف هذه الدراسة إلى معرفة دور النشاط الرياضي الترويحي في التخفيف من بعض المشاكل النفسية لدى المراهقين ، وذلك على عينة قوامها 300 مراهق أختيرت بالطريقة القصدية (ببلديتي مرسى الحجاج -بطيوة بولاية وهران)، وتم استخدام الاستبيان كأداة للدراسة وضم ثلاث محاور هي محور السلوك العدواني، العزلة، الثقة بالنفس وكل محور يتكون من مجموعة من الأسئلة ولغرض تحليل وتفسير النتائج تم استخدام اختبار حسن المطابقة K2 والتكرارات والنسب المئوية عند مستوى دلالة 0.05 ودرجة حرية 01. وخلصنا في الأخير إلى أن للنشاط الرياضي الترويحي دور في التخفيف من بعض المشاكل النفسية لدى المراهقين .وفي الأخير يوصي الباحثون على ضرورة ممارسة النشاط الرياضي الترويحي في أوقات الفراغ. // // // // This study aims to investigate the role of recreational sports activities in alleviating some psychological problems among secondary school students (16-17 years old). The sample consisted of 300 adolescents, selected purposively from secondary school (in the municipalities of Marsa El Hadjadj and Betioua, Oran Province). A questionnaire was used as the study tool, comprising three axes: aggressive behavior, isolation, and self-confidence. Each axis consists of a set of questions. To analyze and interpret the results, the K2 goodness-of-fit test, frequencies, and percentages were used at a significance level of 0.05 and a degree of freedom of 0.01. We concluded that recreational sports activities play a role in alleviating some psychological problems among secondary school students (16-17 years old). Finally, the researchers recommend the necessity of engaging in recreational sports activities during leisure time
MEPS-2025-10
Keywords: النشاط الرياضي الترويحي -المشاكل النفسية // // : recreational sports activities - psychological problems